Game-theory models of interactions between tumour cells. - Tomlinson, I (1997)
The population of cells that comprises a tumour may consist of genetically different individuals. Often, such polymorphisms result from the expansion of a new, advantageous clone. The hypothesis is presented that sometimes tumour cells may adopt genetically-determined strategies to boost their own replication at the expense of other cells in the tumour. Simple game-theory models have been used to study this hypothesis, taking as an example the hypothetical advantage gained by tumour cells which produce a cytotoxin to harm other tumour cells. The models show that genotypes which cause cells to produce cytotoxic substances can spread through the tumour cell population, as can genotypes for resistance to the cytotoxin; in other circumstances, stable polymorphisms between these strategies can occur. The path of the tumour cell population to internal or external equilibrium is often complex, with large fluctuations in genotype frequencies. Flexible strategies are usually superior to fixed strategies. As in populations of whole organisms, 'social' interactions between tumour cells can act in favour of the individual cell at the expense of the tumour as a whole: strategies that retard the growth of the tumour can be selected and tumour regression is theoretically possible. Many mutations in tumours, especially in large or late-stage lesions, may play a role in relations between tumour cells rather than providing those cells with a simple replicative advantage.